Game Edukasi Memilah Sampah - Fadhlanrashif Supriana (Jurnal Sistem Informasi, Sains Data, dan Informatika, 2026)
Waste management issues in Indonesia are rooted in the low level of public understanding regarding waste sorting by type. Conventional education often fails to create engagement, leaving the community unmotivated to practice sorting at the source. This research aims to provide a solution through the application of the Game-Based Learning (GBL) method as an interactive educational medium. The GBL method transforms waste classification materials (organic, inorganic, and hazardous waste) into fun and easy-to-understand game mechanics. Through interactive simulations, players are presented with challenges and instant feedback capable of enhancing information retention and cognitive abilities in virtual waste sorting. The research results are expected to demonstrate that the integration of game elements significantly increases community engagement and understanding compared to static counseling methods. This approach will result in game designs and prototypes developed within the Unity application.